Revisiting the Association between Pornography Use and Risky Sexual Behaviors: The Role of Early Exposure to Pornography and Sexual Sensation Seeking - Sinković, Matija (Array, 2013)
Among the suggested problems and harms associated with widespread pornography use among young people, risky sexual behaviors have been frequently mentioned. To further explore this public health concern, this article analyzed sexual sensation seeking (SSS) as a potential confounder of the association between pornography use and sexual risks using data collected in 2010 from a population-based sample of young Croatian adults aged 18-25 (n=1, 005). Significant, but small, correlations were found between the indicators of pornography use (age at first exposure, frequency of use in the past 12 months, and personal importance of pornography) and sexual risk taking. However, in a multivariate analysis, only age at first exposure to pornography remained a significant, albeit weak, predictor of sexual risk taking among both women and men. SSS, defined as the dispositional tendency toward the impulsive pursuit of sexual arousal and stimulation, neither confounded nor moderated this association. Overall, the findings do not support the notion that pornography use is substantially associated with sexual risk taking among young adults, but suggest that early exposure to sexually explicit material and high SSS are additive risk factors for sexual risk taking.